Spectroscopic investigations of infrared-radiofluorescence (IR-RF) for equivalent dose estimation. (April 2022) - Sontag-González, Mariana; Fuchs, Markus
Abstract: Infrared radiofluorescence (IR-RF) is a technique with the potential to date sediment deposition beyond 1000 Gy. However, the total IR-RF signal is composed of several emissions whose separate characteristics are still poorly understood. We obtained RF emission spectra for two sediment samples dominated by K-feldspar in the wavelengths ∼600–1000 nm over a wide dose range of up to 4000 Gy to discuss possible effects of neighbouring emissions on the conventional IR-RF De estimation via a photomultiplier tube, which yields a signal integration over a wavelength range of more than 30–40 nm. The studied samples included a modern age and a field-saturated one to assess the emissions' characteristics at different dose ranges. For these samples, we find no significant influence of neighbouring emissions to the De obtained from the wavelength range typically used for IR-RF. Highlights: RF emission spectra measured for a modern and a field-saturated sample. Natural IR-RF signal from old sample yields a mean saturation of ∼86%. Wavelength-resolved IR-RF De values similar to those obtained from a PMT. No significant effect from red RF emissions observed on IR-RF De .